TIKTOK-BASED VIDEO TUTORIAL LEARNING MEDIA ON THE TOPIC OF SIMPLE 3D DRAWING WITH CAD - Zadi, Fikran Fauzul; Hamdani, R. Aam (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2024)
This research aims to produce a product in the form of a TikTok-based video tutorial learning media on the topic of basic 3D drawing command functions with CAD, and to determine the feasibility and user response towards this media. The research employs the Design Based Research (DBR) development model, which consists of four stages: problem identification, prototype solution development, testing and solution improvement, and reflection and solution implementation. The testing was conducted in class XI- DGM 1 in the subject of designing techniques with CAM, with a sample size of 35 students. The instrument used was a questionnaire. The research yields a video tutorial learning media based on the TikTok application for basic 3D drawing command functions with CAD. The feasibility assessment conducted by 3 subject-matter experts and 3 media experts indicates that the developed TikTok-based video tutorial learning media is deemed "very feasible." After being approved by the subject-matter and media experts, further testing was carried out in class XI-DGM 1 in the subject of designing techniques with CAM, using a questionnaire as the instrument. The user response results were categorized as "very positive." In conclusion, based on the research findings, this TikTok-based video tutorial learning media is highly suitable for use in teaching designing techniques with CAM.